DEVELOPMENT OF HYPERLINK-BASED AUDIO VISUAL MEDIA FOR SIX-GRADE SCIENCE LEARNING - Ummu Kulsum Syarifah; Ahmad Nur Fatirul; Harwanto Harwanto (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2020)
The ability of teachers as educators in creating a conducive and effective learning atmosphere as well as fun which is the main goal in the learning process. The use of learning media through hyperlink-based audio visual in the learning process is the main choice in generating interest and motivation of students in learning activities. Audio visual media is a multimedia device that integrates various types of media such as the sound of an animated text, video image inserted into the created program. The use of this media is an interactive instructional media which will help the effectiveness of the learning process in delivering the content of the lesson. This study aimed to determine the effectiveness and interest in the use of learning media through hyperlink- based audio visual which was held at SDN Basanah Tanah Merah subdistrict for 20 sixth-grade students learning the science subjects about the solar system in the form of Microsoft power point. This research was a research and development following the model suggested by Dick and Carey. This method was used to generate the product and can be used in education as reference of learning. The results of research indicate that the instructional media through hyperlink- based audio visual used in the activities learning has a high level of effectiveness and interest in students in the learning process activities, especially on science subjects seen from the motivation of students in asking and answering.